The association of short segment Barrett's esophagus with intestinal metaplasia in stomach - İlyas TUNCER; Serdar UĞRAŞ; İsmail UYGAN; Kürşad TÜRKDOĞAN; Mustafa KÖSEM (Turkish Journal of Gastroenterology, 2019)
-